Corporate Finance : The Ultimate Guide to Financial Reporting, Business Valuation, Risk Management, Financial Management, and Financial Statements - Shields, Greg (Bravex)
Contiene: 1) Introducción. 2) Valuación empresarial. 3) Gestión de riesgo. 4) Getsión financiera. 5) Estados financieros.